Production of thermoplastic matrix towpregs for highly demanding and cost-effective commercial applications - Nunes, J. P. (2013)
This work reviews the work made in last years to produce thermoplastic matrix towpregs to highly demanding and more cost-effective commercial applications using a powder coating technology developed in Portugal by Minho and Porto Universities. Different thermoplastic matrices and continuous fibre reinforcements were used in the towpregs produced for highly demanding markets (e.g., carbon fibre reinforced Primospire towpreg) and for more commercial applications (e.g., glass fibre reinforced polypropylene and polyvinyl chloride towpregs). The relevant processing parameters, such as, fibre pull-speed and furnace temperature were varied to determine their influence on the polymer mass fraction obtained in the studied raw materials. Several technologies were also developed and used (compression moulding, pultrusion and filament winding) to process composite parts with adequate properties for the envisaged markets at compatible production rates. The obtained results lead us to conclude that the studied thermoplastic matrix towpregs and their processed composite parts have very interesting conditions for being applied both in highly advanced and cost-effective markets.